2009
DOI: 10.1021/ja9036516
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Montmorillonite Catalysis in the Formation of RNA Oligomers

Abstract: The montmorillonite clay-catalyzed reactions of nucleotides generate oligomers as long as 50-mers. The extent of catalysis depends on the magnitude of the negative charge on the montmorillonite lattice and the number of cations associated with it. When cations in raw montmorillonites are replaced by sodium ions, the resulting Na(+)-montmorillonite does not catalyze oligomer formation because they saturate the interlayers between the platelets of montmorillonites, which blocks the binding of the activated monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 35 publications
2
94
0
Order By: Relevance
“…While the presence of montmorillonite had surprisingly little impact on the evolution of ribozymes that catalyze self-cleavage, it remains to be seen if intermolecular functions such as ligand binding or RNA ligation are more strongly impacted by the presence of this mineral surface. Furthermore, other mineral surfaces, even other classes of montmorillonite, vary in their characteristics (Joshi et al 2009;Swadling et al 2013) and may have different impacts on RNA evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the presence of montmorillonite had surprisingly little impact on the evolution of ribozymes that catalyze self-cleavage, it remains to be seen if intermolecular functions such as ligand binding or RNA ligation are more strongly impacted by the presence of this mineral surface. Furthermore, other mineral surfaces, even other classes of montmorillonite, vary in their characteristics (Joshi et al 2009;Swadling et al 2013) and may have different impacts on RNA evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Montmorillonite clay minerals have been shown to bind RNA (Franchi et al 2003), act as a scaffold to facilitate the formation of RNA from activated monomers (Huang and Ferris 2006;Joshi et al 2009), and support formation of RNA encapsulating vesicles (Hanczyc et al 2003(Hanczyc et al , 2007. At least two biologically derived, functional RNA structures (hammerhead and hairpin ribozymes) remain catalytically active in the presence of montmorillonite clay (Biondi et al 2007a,b); however, it is unclear whether these two structures from contemporary biology are representative of ribozymes in general.…”
Section: Introductionmentioning
confidence: 99%
“…For Model I, there is evidence that RNA synthesis is facilitated on catalytic surfaces such as montmorillonite clays or other crystal surfaces (Vlassov et al, 2005;Ferris & Delano, 2008, Joshi et al, 2009. De Roos postulated a PCR-like mechanism (De Roos, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that montmorillonites with smaller surface layer charges are better catalysts. [118][119][120] By studying the oligomerization reaction of ImpU and ImpA inhibited by N 6 ,N 6 -dimethyladenine and dA 5 ' ppdA on montmorillonite, it was found that activated RNA mon- omers (ImpU and ImpA) bind only to the silicate surface of the clay interlayer, on catalytic sites about 1.5 nm apart (1-2 • 10 14 sites per milligram). 121 On clay surfaces, purine nucleotides bind more strongly and are oriented differently than those of pyrimidine.…”
Section: +mentioning
confidence: 99%